(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The purpose of the study is to find out the consumer’s buying preference and reason for purchasing the organic personal care products. Personal care means external care to the body, appearance and hygiene. Organic personal care products are develop in the form of agricultural ingredients grown in the absence of pesticides, synthetic fertilizers genetically modified organism and radiation.Now a days, the younger generations are given more importance to their body and skin for that they used to prefer organic and natural cosmetics and skin care products. Organic personal care product provide natural protection to the skin and also help as keep our well-being in- check. Natural or organic cosmetics are not just beauty products, but a reaction of nature in perfect harmony with our bodies and our world.The study contains primary and secondary data. 60 respondents were selected as sample by using convenient sampling method in Nagercoil town. The study found that consumer is giving more preference to hair care under personal care which was influenced by fragrance and no side effects.